Functional and cognitive decline in hospitalized elderly - Mendes, Eugénia (2014)
A descriptive and correlational study was conducted. Functional and cognitive status was measured at admission and discharge, using the Functional Independence Measure (FIM) and the Mini-Mental State Examination (MMSE), in elderly patients with gastroenterological and respiratory disorders admitted in an internal medicine unit. Were included 51 elderly (75.53±7.16 years), 53% women, with a length of stay of 14.27±6.45 days. Results show a significant decrease of scores from admission to discharge in FIM (t=3.78; p=0.00), FIM cognitive (t=4.14; p=0.00), FIM motor (t=3.24; p=0.041) and in MMSE (t=5.47; p=0.00). Negative correlations between age and length of stay and the scores of all measures were found. Better scores, with significant differences between means, were obtained by the participants living at home when compared with institutionalized ones (FIM t=2.30; p=0.039 vs t=2.45; p= 0.03; MMSE t=3.26; p=0.002 vs t=3.42; p=0.001). Hospitalization contributes to a greater weakness/frailty of the elderly and is considered high risk for decline in physical fitness and cognitive function. This study highlights the importance of assessment of functional capacities in elderly patients.